Effect of Cryopreservation According Two-Stage Program in High-Molecular Dextran Solutions on Cytomorphological and Functional Properties of Human Cord Blood Cells - Kozhina, Olga Yu.; Ostankov, Maksim V.; Grisha, Igor G.; Bondarovich, Nikolay A. (Problems of Cryobiology and Cryomedicine, 2013)
Human cord blood (HCB) is a conventional source of stem cells and biologically active substances. Long-term storage of this unique biomaterial is possible under conditions of low temperature bank. In this research we studied the effect of cryopreservation according to two-stage freezing program on cytomorphological and functional characteristics of cells of HCB leukoconcentrate (HCBL). It was shown that after cryopreservation under protection of high molecular dextran, redistribution in cell composition of HCBL occurred due to reduction of granulocytes population, increase of non-differentiated cells and macrophages number. Quite a high resistance to effect of cryopreservation factors had stem and early progenitor cells. There was noted a reduction of total bactericidal activity of HCBL cells and increase of phagocytic activity of macrophages. Probl Cryobiol Cryomed 2013; 23(1):58–65.